Exploitation of Heterosis in Single Cross Hybrids of Quality Protein Maize (Zea maize L.) for Yield and Quality Traits - Bisen, Prashant; Dadheech, Amit; Namrata; Nagar, Omprakash; Meena, Ram Kunwar (International Journal of Bio-resource and Stress Management, 2023)
Forty-five single-cross hybrids developed from ten inbred lines of quality protein maize through diallel mating design along with four checks viz., Pratap QPM Hybrid-1, Vivek QPM-9, HQPM-1 and HQPM-5 were evaluated in randomized block design with three replications for seventeen traits during kharif-2014, to identify the heterotic superiority of the New cross combinations over the parents and best check. Out of 45 crosses, 42 crosses over mid parent, 37 crosses over better parent and 6 crosses over standard check (HQPM-5) significantly out yielded for grain yield plant-1. Hybrid P6×P8 showed maximum per se performance for grain yield plant-1, stover yield plant-1, ear length, ear girth and tryptophan content also showed good per se performance for oil content (6.13%), starch content (69.83%), protein content (10.52%) and for lysine content (4.19%) with maximum positive significant economic heterosis (19.63%) for grain yield plant-1, over the best check HQPM-5. Hybrid P5×P8 showed highest per se performance along with maximum positive significant economic heterosis for lysine content and protein content over the best check Vivek QPM-9 and HQPM-5, respectively. Another hybrid P3×P5 and P5×P7 exhibited highest per se performance for oil content and starch content, respectively, along with maximum positive significant economic heterosis over the best check HQPM-5 and HQPM-1, respectively.